AI in Education: A Threat to Teachers or a Tool for Enhancing Learning? - Huda, Moh. Choirul (STKIP PGRI Tulungagung, 2025)
Artificial Intelligence (AI) is playing an increasingly important role in education, changing how students learn and how teachers teach. This essay explores both the opportunities and risks of using AI in schools. On the positive side, AI supports personalized learning by adjusting materials based on students’ needs, helps teachers by automating routine tasks, and improves access for students in remote areas or with special needs. When used effectively, AI can make education more inclusive, efficient, and flexible. To examine these issues, this essay applies a descriptive–analytical–argumentative method. It begins by explaining how AI is used in education, then analyzes both its benefits and drawbacks, and finally presents a reasoned position supported by academic literature and real-world examples. The essay draws on sources from both international and Indonesian contexts to ensure relevance and balance. This topic is significant because AI adoption in education is growing rapidly, yet many institutions and educators are not fully prepared to face its ethical, pedagogical, and technological challenges. Therefore, it is suggested that schools, policymakers, and teacher-training institutions work together to create clear guidelines, ensure ethical data use, and equip teachers with the necessary skills. A thoughtful, human-centered approach is essential to ensure that AI enhances, rather than replaces, the irreplaceable role of educators.